PENGARUH KOMBINASI PUPUK KANDANG KAMBING, PUPUK HAYATI DAN KAPUR TERHADAP PERTUMBUHAN DAN HASIL DUA VARIETAS KUBIS BUNGA PADA LAHAN SULFAT MASAM DENGAN SISTEM BUDIDIDAYA JENUH AIR - Randi Risantho Sihotang; Dini Anggorowati; Nurjani Nurjani; Dwi Zulfita (Agros Journal of Agriculture Science, 2024)
The Cauliflower (Brassica oleraceae var botrytis L.) is a potential horticultural commodity that has great prospects for intensive development in the lowlands. The vitamin and fiber content in cauliflower is so abundant that it is very good for the human body. Cauliflowers can be cultivated on several types of mineral soil, one of which is acid sulfate mineral soil. Problems in acid sulfate mineral soils contain high clay, high soil acidity, a pyrite layer, and nutrient deficiencies. Efforts can be made to support the growth of cauliflower by applying a soil saturated culture system, providing combination of goat manure + bioboost + dolomite, and using lowland cauliflower varieties. The research location is at Golden River Camp Kalimas Village, Sungai Kakap District, Kubu Raya Regency. The research took place from July to November, 2023. The research design used was a Split Block Design, consisting of 2 treatment factors and repeated 3 times and consisting of 4 sample plants. The first factor is the variety as the main plot with 2 treatment levels (Larissa and Snow White) and the second factor is the combination of ts (goat manure ton/ha + bioboost ml/l + dolomite ton/ha) as a subplot with 4 treatment levels. The variables observed in this study consisted of the number of leaves (strands), leaf area (cm2), fresh weight of upper plants (g), dry weight of upper plants (g), age of flower appearance (hst), crop diameter (g) and crop weight (g). The results showed that there was a different response between the two varieties and the combination of goat manure + bioboost + dolomite on the growth and yield of cauliflower, The Larissa variety showed better growth and yield when compared to the Snow white variety and the combination of goat manure 10 tons/ha + bioboost 15 ml/l + dolomite 2 tons/ha can increase the growth and yield of cauliflower better than other ts combinations on tidal acid sulphate soil with soil  saturated culture system.